SPE Reservoir Simulation Conference 2017
DOI: 10.2118/182603-ms
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Capillary Pressure and Critical Property Shift due to Confinement on Hydrocarbon Production in Shale Reservoirs

Abstract: This thesis marks the end of a great chapter of my life and the beginning of several stellar possibilities. My two years at Stanford have changed my life and the knowledge I have gained will certainly brighten my future paths like never before. My thanks to Energy Resources Engineering, Reservoir Simulation Industrial Affiliates (SUPRI-B) program and ENI for funding my MS and Stanford Summer Tutorial program which gave me one of the best experiences of lecturing Stanford students in my final quarter of MS. I w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Saturated bulk pressure and saturated confined pressure are often compared in the literature in studies using EOS modification by critical point shift [14,16,20,23,25,26,27] or capillary pressure method [14,15,16,17,18,19,20,21,22]. Comparison between classic EOS and modified EOS for confined fluid modeling showed that the bubble point pressure decreases with confinement.…”
Section: Considerations Of the Reference Pressure In Confinementmentioning
confidence: 99%
See 2 more Smart Citations
“…Saturated bulk pressure and saturated confined pressure are often compared in the literature in studies using EOS modification by critical point shift [14,16,20,23,25,26,27] or capillary pressure method [14,15,16,17,18,19,20,21,22]. Comparison between classic EOS and modified EOS for confined fluid modeling showed that the bubble point pressure decreases with confinement.…”
Section: Considerations Of the Reference Pressure In Confinementmentioning
confidence: 99%
“…Secondly, a lot of work has been done on extension of equations of state (EOS) for confined fluid behavior modeling. The first main method used includes capillary pressure in the flash calculation considering two phases in equilibrium having two different pressures [14,15,16,17,18,19,20,21,22]. Some authors improve this method by considering the thickness of the adsorbed layer [23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cubic EOS that uses pressure–volume–temperature (PVT) is widely used to describe fluid properties, such as Van der Waals EOS, Soave modification of Redlich–Kwong (SRK), Peng–Robinson (PR) EOS, et al . The PR EOS exhibits performance similar to that of the SRK equation for the most part, and the SRK EOS has been used to study the confinement effect in this paper, and has been widely used for oil reservoir simulation tools . The parameters are generally determined by the physical laboratory measurements (such as PVT cell) using the bulk fluid.…”
Section: Introductionmentioning
confidence: 99%
“…The cubic EOS that uses pressure-volume-temperature (PVT) is widely used to describe fluid properties, such as Van der Waals EOS, Soave modification of Redlich-Kwong (SRK), Peng-Robinson (PR) EOS, et al [7][8][9][10] The PR EOS exhibits performance similar to that of the SRK equation for the most part, and the SRK EOS has been used to study the confinement effect in this paper, and has been widely used for oil reservoir simulation tools. [11][12][13][14] The parameters are generally determined by the physical laboratory measurements (such as PVT cell) using the bulk fluid. Besides, the SRK EOS introduces the interaction factor of fluid molecules and ignores the molecular-wall collision factor, which means that it should be improved for it to be applied for numerical simulation of tight oil reservoir development.…”
Section: Introductionmentioning
confidence: 99%